(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate the effect of OO and FO based LEs on morbidities in preterm infants. Materials and Methods: A total of 44 neonates with a gestation ≤32 weeks were included in this retrospective observational study. The study group composed of neonates (n=28) who received SMOFlipid and the control group consisted of infants (n=16) who received ClinOleic. Demographic and clinical data of the neonates in terms of duration of PN, respiratory distress syndrome (RDS), bronchopulmonary dysplasia (BPD), ), duration of mechanical ventilation (MV), patent ductus arteriosus (PDA), necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH), retinopathy of prematurity (ROP), PN-associated cholestasis (PNAC) and plasma triglyceride (TG) levels (mg/dl) were collected and compared statistically. Results: We did not find significant difference in terms of RDS, BPD, NEC, IVH, ROP and PNAC. The study group had lower TG levels than the control group which were 93.03±24.55 mg/dL and 151.31±114 mg/dL, respectively (p=0.002). Conclusion: Both LEs are well tolerated and safe without any side effects in preterm infants. Although both LEs have no significant effect on morbidities, FO based LE provide better TG levels than OO based LEs.